Syariah courts and issues on administration of Syariah criminal justice in Malaysia - Shuaib, Farid Sufian (The Malaysian Current Law Journal Sdn. Bhd., 2018)
The administration of Islamic law is focused on Syariah courts. Be that as it may, in considering the development and issues of Islamic law in Malaysia, one could not run from discussing the position of Syariah courts. The chapter seeks to examine the impact on the dual legal system operating in parallel to each other in Malaysia to the administration of Islamic criminal law in Malaysia. It also looks at the improvement that could be made to the administration of justice.